2009
DOI: 10.1007/s00240-009-0228-y
|View full text |Cite
|
Sign up to set email alerts
|

Electrical conductivity and total dissolved solids in urine

Abstract: The objective of this paper is to study the relevance of electrical conductivity (EC) and total dissolved solids (TDS) in early morning and random samples of urine of urinary stone patients; 2,000 urine samples were studied. The two parameters were correlated with the extent of various urinary concrements. The early morning urine (EMU) and random samples of the patients who attended the urinary stone clinic were analysed routinely. The pH, specific gravity, EC, TDS, redox potential, albumin, sugar and microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 7 publications
3
28
0
Order By: Relevance
“…Our results indicated that U EC is a clinically useful method for assessing UC in dairy cattle. The median value for U EC in periparturient dairy cattle was 23.7 mS/cm, which was similar to the mean value for urine from adult humans in India (21.6 mS/cm), 17 and Turkey (25.5 mS/cm), 19 but greater than that reported for children in Turkey (9.1 mS/cm). 18 We found a good association (r s = 0.70) between U EC and U Osm that was consistent with studies in human urine, where correlation coefficients ranged from 0.67 to 0.91.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Our results indicated that U EC is a clinically useful method for assessing UC in dairy cattle. The median value for U EC in periparturient dairy cattle was 23.7 mS/cm, which was similar to the mean value for urine from adult humans in India (21.6 mS/cm), 17 and Turkey (25.5 mS/cm), 19 but greater than that reported for children in Turkey (9.1 mS/cm). 18 We found a good association (r s = 0.70) between U EC and U Osm that was consistent with studies in human urine, where correlation coefficients ranged from 0.67 to 0.91.…”
Section: Discussionsupporting
confidence: 76%
“…15 Urine electrical conductivity is a nonlinear function of the number of electrically charged particles. 16,17 Urine electrical conductivity (U EC ) has been evaluated in several studies as an indirect method for assessing UC in humans. [17][18][19][20] However, the clinical performance of U EC does not appear to have been investigated in ruminant urine.…”
Section: Introductionmentioning
confidence: 99%
“…Urine conductivity depends on the charge and concentration of the charged particles of different sizes in urine [17,18]. Figure 1(b) compares the conductivity changes in different particle sizes between the two types of urinary crystallites.…”
Section: Conductivity Changesmentioning
confidence: 99%
“…When the precipitation of calcium oxalate appeared, the ions in solution decreased, so the electrical conductivity decreased, while the rate of decline of conductivity changes may reflect the different crystallization conditions [4] . There are some studies on kinetics of formation of calcium oxalate crystal by solution conductivity measurement which is a simple, cheap and not time consuming method [5] . For quick comparison of taurine and taurine Magnesium regulation of calcium oxalate crystal growth, conductivity method also could be applied to this research.…”
Section: Introductionmentioning
confidence: 99%